Towards a Water-Secure Kenya : Water Resources Sector Memorandum - World Bank (Washington, DC, 2013)
The main objective of the Water Resources Sector Memorandum (WRSM) is to capture the emerging water resources management priorities and to propose a plan of action that will put water resources management on a sound footing in Kenya. It will also guide the engagement of development partners who are formulating programs for supporting reforms and investments in water resources management and development. The WRSM provides an economic rationale for extending the water resources reforms being undertaken by the Government of Kenya and highlights the need to broaden the ownership of the reforms to include other sectoral ministries, NGOs, the private sector, and community groups. It broadens and complements the analyses of water issues in the Country Economic Memorandum (CEM) and will inform the Country Assistance Strategy (CAS).